2003
DOI: 10.1097/01.ccm.0000050454.01978.3b
|View full text |Cite
|
Sign up to set email alerts
|

2001 SCCM/ESICM/ACCP/ATS/SIS International Sepsis Definitions Conference

Abstract: This document reflects a process whereby a group of experts and opinion leaders revisited the 1992 sepsis guidelines and found that apart from expanding the list of signs and symptoms of sepsis to reflect clinical bedside experience, no evidence exists to support a change to the definitions. This lack of evidence serves to underscore the challenge still present in diagnosing sepsis in 2003 for clinicians and researchers and also provides the basis for introducing PIRO as a hypothesis-generating model for futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
2,835
3
124

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 5,105 publications
(2,985 citation statements)
references
References 35 publications
23
2,835
3
124
Order By: Relevance
“…The ICU characteristics are presented in Table 1. The JSEPTIC DIC study included 3,195 consecutive adult patients with severe sepsis or septic shock, which was defined on the basis of the International Sepsis Definitions Conference criteria,22 diagnosed between January 2011 and December 2013. The JSEPTIC DIC study excluded patients who were <16 years old or patients who developed severe sepsis or septic shock following ICU admission.…”
Section: Basic Information Regarding the Jseptic Dic Studymentioning
confidence: 99%
“…The ICU characteristics are presented in Table 1. The JSEPTIC DIC study included 3,195 consecutive adult patients with severe sepsis or septic shock, which was defined on the basis of the International Sepsis Definitions Conference criteria,22 diagnosed between January 2011 and December 2013. The JSEPTIC DIC study excluded patients who were <16 years old or patients who developed severe sepsis or septic shock following ICU admission.…”
Section: Basic Information Regarding the Jseptic Dic Studymentioning
confidence: 99%
“…We looked at patients with sepsis compared with three control groups: adults not currently in hospital, patients in hospital with non-sepsis infection, and patients in hospital with an acute sterile inflammatory process. These comparisons allowed us to determine the excess mortality associated with sepsis (including that associated with admission to hospital) and the incremental excess mortality associated with sepsis, beyond what is associated with admission for the two cardinal features of sepsis11 13 14: infection (by comparing sepsis with inflammatory conditions not caused by infection) and inflammation (by comparing sepsis with infections without evidence of inflammatory storm).…”
Section: Introductionmentioning
confidence: 99%
“…8 JAAM‐SR‐Advanced also reported that the mortality rate of patients with septic shock was twice as high as those without it. 9 Nevertheless, the definition of septic shock is “refractory hypotension remaining after adequate fluid resuscitation,”14 and there is subjective discretion with regard to the amount and interval of “adequate fluid resuscitation.” Based on our results, this new outcome indicator, which combines initial hypotension and hyperlactemia ≥4 mmol/L, is thought to be objective and potentially more reliable and useful than the term “septic shock.” Furthermore, if we can utilize the initial lactate values instead of the worst lactate values over 24 h, it would be possible to predict patient outcomes more precisely at the time of admission.…”
Section: Discussionmentioning
confidence: 99%
“…Definitions of severe sepsis and septic shock were according to the 2003 revision of the definitions by the American College of Chest Physicians/Society of Critical Care Medicine Consensus Conference 13, 14. Initial hypotension was defined as a systolic blood pressure (SBP) <90 mmHg or a MBP <65 mmHg 14…”
Section: Methodsmentioning
confidence: 99%